2022
DOI: 10.3390/su14159645
|View full text |Cite
|
Sign up to set email alerts
|

Floating TiO2-Cork Nano-Photocatalysts for Water Purification Using Sunlight

Abstract: In the present study, titanium dioxide (TiO2) nano-photocatalysts were synthesized through microwave irradiation. In a typical microwave synthesis, TiO2 nanomaterials were simultaneously produced in powder form and also directly covering cork substrates. The TiO2 nanopowder was analyzed by X-ray diffraction (XRD), Raman spectroscopy and transmission electron microscopy (TEM), revealing that the solvothermal microwave synthesis resulted only in the TiO2 anatase phase. From Fourier-transform infrared spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 116 publications
1
6
0
Order By: Relevance
“…In accordance with the SEM results, it can be observed that the g-C 3 N 4 sheets are covered with TiO 2 nanostructures—however, not forming a continuous film—and larger agglomerates are also detected ( Figure 4 a–f) but, as observed previously, are expressively smaller than those for the pure TiO 2 material. As reported in an analogous study [ 86 ], it can be seen that these agglomerates are formed by very fine TiO 2 nanoparticles with irregular shapes, where near spherical nanocrystals and more elongated ones can be observed ( Figure 4 g–i). The average TiO 2 particle size was found to be 5.17 ± 1.37 nm, and it can be seen from the particle size distribution (inset of Figure 4 d) that smaller particles in the range of 4–7 nm are more likely to be found.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…In accordance with the SEM results, it can be observed that the g-C 3 N 4 sheets are covered with TiO 2 nanostructures—however, not forming a continuous film—and larger agglomerates are also detected ( Figure 4 a–f) but, as observed previously, are expressively smaller than those for the pure TiO 2 material. As reported in an analogous study [ 86 ], it can be seen that these agglomerates are formed by very fine TiO 2 nanoparticles with irregular shapes, where near spherical nanocrystals and more elongated ones can be observed ( Figure 4 g–i). The average TiO 2 particle size was found to be 5.17 ± 1.37 nm, and it can be seen from the particle size distribution (inset of Figure 4 d) that smaller particles in the range of 4–7 nm are more likely to be found.…”
Section: Resultssupporting
confidence: 79%
“…After this time, a transparent solution could be observed ( Figure S3f ). The MO degradation ratio (%) was calculated based on Equation (2): where is the initial absorbance of the MO solution before irradiation, and is the absorbance of the MO solution after a certain exposure time (t) [ 23 , 78 , 86 , 113 , 114 ]. Based on Figure S3a–e , it is possible to calculate the ratio between the maximum value of each absorbance spectrum ( ) at each exposure time and the initial absorbance of the solution ( ), as depicted in Figure 10 a.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations